Profil Ayah dalam Novel Ayahku (Bukan) Pembohong Karya Tere Liye: Tinjauan Sosiologi Sastra - Mariani, Fepi; Nurizzati, Nurizzati; Afnita, Afnita (Universitas Negeri Padang, 2012)
This research is intended to describe about: (1) the profile of father in novel Ayahku (Bukan) Pembohong written by Tere Liye; (2) the cultural aspect in novel Ayahku (Bukan) Pembohong written by Tere Liye; (3) the relation between father’s profile in novel Ayahku (Bukan) Pembohong written by Tere Liye and father in reality viwed from literature-sociology. The data in this study was the intrinsic unsures that support the make of novel Ayahku (Bukan) Pembohong. They are characters, plot, setting and theme. The data was gotten from novel Ayahku (Bukan) Pembohong written by Tere Liye, in 299 pages. It was published by Gramedia Pustaka Utama, fourth edition on August 2011 in Jakarta. The finding is the father’s profile that was found on that novel, there are cultural aspect and relation between father’s provile on novel and father in reality.